Evaluation of the effect of different rubber dam clamps on the mandibular first molar with Finite element analysis - Eskibaglar, Mehmet; Erdem, Serkan; Kaman, Mete Onur (Taylor & Francis Ltd, 2024)
The aim of this study was to evaluate the stress induced by clamps made of different materials on mandibular first molar teeth using finite element analysis. The tooth model to be used in the study was created using micro-CT scanner and the rubber dam clamp model was created in three dimensions (3D) using Solidworks and applied to a finite element tooth model of an intact mandibular first molar. The size of the clamp opening and the force to be applied were calculated according to the buccolingual distances of the tooth. The contact areas of the clamps on the tooth were determined and subjected to force. The stress distribution patterns and maximum von Mises stresses were calculated and compared against these forces. The most stress against these forces occurred in the enamel tissue on the distal side where the clamp was in contact with the tooth. The stress value in the stainless steel clamp (191.63 MPa) was approximately 85% higher than the clamp made of polyethylene ketone (103.85 MPa). The stress in the dentin and pulp tissue of the tooth was negligible. Clinicians should examine the enamel tissue below the equatorial line of the tooth in detail before clamp application. The forces exerted by stainless steel clamps can cause damage to the enamel tissue of the tooth or progression of an existing enamel crack.
Keywords: Biomechanics; finite element analysis; rubber dam clamp; stress